Synthesis of Epoxyisoprostanes: Effects in Reducing Secretion of Pro‐inflammatory Cytokines IL‐6 and IL‐121. Issue 20 (16th April 2013) - Egger, Julian; Bretscher, Peter; Freigang, Stefan; Kopf, Manfred; Carreira, Erick M.
<x xml:space="preserve">Abstract</x> Anti‐inflammatory: The efficient and general synthetic route to the elusive epoxyisoprostanoid phospholipids PECPC and PEIPC, along with the isoprostanoids EC and EI, relies on a number of stereo‐ and chemoselective steps, including a CH insertion for the rapid construction of the cyclopentanone ring. The synthesized compounds display unprecedented biological activity in reducing the secretion of pro‐inflammatory cytokines.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>